2021
DOI: 10.1007/s00404-021-06299-x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of perioperative complications associated with retropubic tension-free vaginal tape in 960 women

Abstract: Purpose The purpose is to analyse perioperative complications associated with the retropubic tension-free vaginal tape (TVT) procedure and their management. Methods This retrospective, monocentric cohort study included 960 women after retropubic TVT procedure performed by one surgeon from 2011 to 2016. Complications were identified up to 6 weeks after the procedure, divided into specific and general complications and classified based on the Clavien–Dindo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…It is well-known that urinary retention and voiding dysfunction are the most common complications following the MUS procedure [12,13], which is in line with the data presented in this study. The higher incidence of postoperative voiding dysfunction in our cohort compared to the literature [4,12] might be attributed to a standardized and precise postoperative control via transvaginal ultrasound.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is well-known that urinary retention and voiding dysfunction are the most common complications following the MUS procedure [12,13], which is in line with the data presented in this study. The higher incidence of postoperative voiding dysfunction in our cohort compared to the literature [4,12] might be attributed to a standardized and precise postoperative control via transvaginal ultrasound.…”
Section: Discussionsupporting
confidence: 92%
“…While the incidence of postoperative voiding dysfunction was higher than in the literature, only 1.3% of our patients required revision surgery with tape mobilization. This is lower compared to the studies of Barisiene et al and Jahn et al, which showed rates of 2.4-3.5% [12,13].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The MUS is a safe procedure, but does have some potential complications, both intra- and postoperatively [ 2 , 7 ]. The most common complications are urgency, hematomas, bleeding, postoperative urinary retention (POUR), infections, and vaginal MUS exposure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%